The Impact of Type 1 Interferons on Alveolar Macrophage Tolerance and Implications for Host Susceptibility to Secondary Bacterial Pneumonia - Connolly, Emma; Hussell, Tracy (Frontiers in Immunology, 2020)
That macrophages adapt to environmental cues is well established. This adaptation has had several reiterations, first with innate imprinting and then with various combinations of trained, tolerant, paralysed or primed. Whatever the nomenclature, it represents a macrophage that is required to perform very different functions. First, lung macrophages are one of the sentinel cells that flag up damage and release mediators that attract other immune cells. Next, they mature to support T cell priming and survival. Finally they are critical in clearing inflammatory immune cells by phagocytosis and extracellular matrix turnover components by efferocytosis. At each functional stage they alter intrinsic components to guide their activity. Training therefore is akin to changing function. In this review we focus on the lung and the specific role of type I interferons in altering macrophage activity.